The Design and Development of a Semantic File System Ontology - Mashwani, S. R.; Khusro, S. (Engineering, Technology & Applied Science Research, 2018)
Semantic File System (SFS) is the vision for the future of file systems where information is given with explicit meaning to be processed by machines automatically and consumed by the users easily. SFSs extend traditional file systems to organize and retrieve information according to their semantics, intent and relationships with other resources rather than their physical locations. Ontology-based file system is a step to dissolve the borders between semantic web and semantic desktop to make the desktop part of a single giant web. Unfortunately, to the best of the authors’ current knowledge, so far, no effort has been exercised to develop an ontology for SFSs. This work contributes a SFS ontology, which extends NEPOMUK information element ontology framework into the domain of SFSs. The proposed SFS ontology is freely available with full technical definitions of terms and complete class hierarchy to be used for any purpose in information technology (IT). In addition, as a proof-of-concept implementation, we deploy the proposed ontology in the 360ᵒ SFS. Finally, to get most of the benefits of the ontology, this paper also presents a semantics-aware file manager.